Analysis of Determinants that Influence on Development of the Participants Family of the BPJS Health Recipient Dues (PBI) in Balongrejo Village, Bagor Subdistrict, Nganjuk District - Pety Merita Sari; Nurdina Nurdina; Sandu Siyoto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The toddler period is an important period to determine the quality of the future of the child during this time the development process runs quickly. One of the things we have to ask is the development of toddlers from poor families from the family of BPJS PBI. The purpose of this study was to analyze the factors that support the development of toddlers in the families of PBI BPJS participants in Balongrejo Village. The research design uses Cross sectional. The study population was all toddler in the BPJS PBI family in Ds. Balongrejo. With a sample of 106 respondents using the Simple Random sampling technique. Independent variables were nutritional status, food intake, infectious disease and knowledge. Dependent variable development of toddlers. The instrument uses questionnaire sheets and observation sheets, analyzed using Ordinal Regression test The results of the study are based on the ordinal regression test simultaneously all variables affect the development with the value of Sig. (2-tailed) = 0,000 <0,05, partially the history of infectious diseases and parental knowledge of children under five does not affect development with values. Sig (2-tailed) = 0.148> 0.05 and sig (2-tailed) = 0.996> 0.05, nutritional status and food intake influence the development with the Sig. (2-tailed) = 0,000 <0,05, nutritional status has a greater influence than food intake. Having a good nutritional status 1.3 times can have the opportunity to improve the development process of toddlers. Providing health education to mothers about the importance of fulfilling nutrition, development, and active posyandu activities can reduce developmental deviations of toddler.